The usage of pink public transportation (PPT) among women users - Wok, Saodah; Arzeman, Akmal; Ma, Feiya; Saleh, Nurfatimah Nasution; Zainal Abidin, Nurul Naimah; Mohamad Jumaidi, Siti Nuradlina (Pacific and Asian Communication Association, UPM, 2020)
Public transportation is a service that has been in demand among many people in Malaysia, and Kereta Api Tanah Melayu (KTM) Komuter is one of the public transportation systems. After the establishment of the KTM Komuter, the Malaysian government decided to introduce the Ladies Coach or Pink Public Transportation (PPT) by KTM in 2010 to promote women’s rights. This paper aims to study the usage of PPT among women users and to determine the level of perceived usefulness, perceived ease of use, attitude, and usage of the PPT. This study employed a quantitative research design with a survey method using a self-administered questionnaire to collect data from women users of PPT. A total of 400 respondents participated in this study. Results show that most of the women users find the PPT useful in avoiding harassment and improving women’s safety, thus helping to reduce sexual harassment. It is hoped that the government will enforce the implementation of the PPT to ensure women’s right to safety as well as promoting and publicizing more information about PPT.